Convection-enhanced delivery of M13 bacteriophage to the brain - Ksendzovsky, Alexander (2012)
OBJECT: Recent studies indicate that M13 bacteriophage, a very large nanoparticle, binds to β-amyloid and α-synuclein proteins, leading to plaque disaggregation in models of Alzheimer and Parkinson disease. To determine the feasibility, safety, and characteristics of convection-enhanced delivery (CED) of M13 bacteriophage to the brain, the authors perfused primate brains with bacteriophage. METHODS: Four nonhuman primates underwent CED of M13 bacteriophage (900 nm) to thalamic gray matter (4 infusions) and frontal white matter (3 infusions). Bacteriophage was coinfused with Gd-DTPA (1 mM), and serial MRI studies were performed during infusion. Animals were monitored for neurological deficits and were killed 3 days after infusion. Tissues were analyzed for bacteriophage distribution. RESULTS: Real-time T1-weighted MRI studies of coinfused Gd-DTPA during infusion demonstrated a discrete region of perfusion in both thalamic gray and frontal white matter. An MRI-volumetric analysis revealed that the mean volume of distribution (Vd) to volume of infusion (Vi) ratio of M13 bacteriophage was 2.3 ± 0.2 in gray matter and 1.9 ± 0.3 in white matter. The mean values are expressed ± SD. Immunohistochemical analysis demonstrated mean Vd:Vi ratios of 2.9 ± 0.2 in gray matter and 2.1 ± 0.3 in white matter. The Gd-DTPA accurately tracked M13 bacteriophage distribution (the mean difference between imaging and actual bacteriophage Vd was insignificant [p > 0.05], and was −2.2% ± 9.9% in thalamic gray matter and 9.1% ± 9.5% in frontal white matter). Immunohistochemical analysis revealed evidence of additional spread from the initial delivery site in white matter (mean Vd:Vi, 16.1 ± 9.1). All animals remained neurologically intact after infusion during the observation period, and histological studies revealed no evidence of toxicity. CONCLUSIONS: The CED method can be used successfully and safely to distribute M13 bacteriophage in the brain. Furthermore, additional white matter spread after infusion cessation enhances distribution of this large nanoparticle. Real-time MRI studies of coinfused Gd-DTPA (1 mM) can be used for accurate tracking of distribution during infusion of M13 bacteriophage.